Supramolecular chemistry : from concepts to applications - Kubik, Stefan (De Gruyter Textbook, 2020)
This book is an excellent introduction to supramolecular chemistry, explaining how molecules can be arranged to more complex chemical systems through non-covalent interactions and what makes supramolecular architectures stable. Starting with the principles of molecular recognition and supramolecular receptors, the author further gives an overview of different supramolecular systems and methods for their synthesis.